2017
DOI: 10.1080/02713683.2017.1373824
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of retinal and choroidal structural changes by optical coherence tomography in patients with chronic obstructive pulmonary disease

Abstract: The study results revealed significant average, nasal RNFL, global GCL+ loss, and a nonsignificant choroidal thinning in patients with COPD compared to healthy subjects. The eye seems to be one of the affected tissues during the natural course of the COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 31 publications
5
34
2
Order By: Relevance
“…This is in line with findings from the study of Gok et al. (), in which no significant difference was found in choroidal thickness of patients with mild to very severe COPD compared to matched controls. They also found no relationship between choroidal thickness and COPD severity (Gok et al.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with findings from the study of Gok et al. (), in which no significant difference was found in choroidal thickness of patients with mild to very severe COPD compared to matched controls. They also found no relationship between choroidal thickness and COPD severity (Gok et al.…”
Section: Methodssupporting
confidence: 93%
“…They also found no relationship between choroidal thickness and COPD severity (Gok et al. ). Ugurlu and coworkers reported no significant difference in choroid thickness between a group of male COPD patients and male controls (Ugurlu et al.…”
Section: Methodsmentioning
confidence: 98%
“…Ozcimen et al and Gok et al found the mean RNFL thickness in patients with COPD to be significantly lower . Ugurlu et al also detected lower RNFL thickness in all segments in COPD patients but a significant thinning was only present in the inferior segment .…”
Section: Discussionmentioning
confidence: 90%
“…EDI mode, which is a newly defined method in OCT uses longer wavelength to investigate the choroidal tissues can detect the thickness of choroid tissue peripapillary or subfoveally . In the study by Gok et al; macular choroid thickness values in all COPD stages were reported to be lower than in the control group at all locations, but no statistically significant difference was present . Ugurlu et al reported no statistically significant difference in terms of SFCT between COPD patients and the control group .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation